2015
DOI: 10.1152/ajplung.00276.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperoxic lung injury favorably alters adult right ventricular remodeling response to chronic hypoxia exposure

Abstract: The development of pulmonary hypertension (PH) requires multiple pulmonary vascular insults, yet the role of early oxygen therapy as an initial pulmonary vascular insult remains poorly defined. Here, we employ a two-hit model of PH, utilizing postnatal hyperoxia followed by adult hypoxia exposure, to evaluate the role of early hyperoxic lung injury in the development of later PH. Sprague-Dawley pups were exposed to 90% oxygen during postnatal days 0-4 or 0-10 or to room air. All pups were then allowed to matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 57 publications
1
47
1
Order By: Relevance
“…1. Maximal aerobic capacity (V O2max, expressed relative to body mass) was determined before Su5416 administration and at the end of the 7-wk SuHx period via an indirect open-circuit calorimetric system, as described previously (7,11,16). V O2max was identified using standard criteria for rats, including three consecutive failures to return to running after contacting the shock stimulus at the rear of the treadmill and a respiratory exchange ratio Ͼ 1.015 (4).…”
Section: Methodsmentioning
confidence: 99%
“…1. Maximal aerobic capacity (V O2max, expressed relative to body mass) was determined before Su5416 administration and at the end of the 7-wk SuHx period via an indirect open-circuit calorimetric system, as described previously (7,11,16). V O2max was identified using standard criteria for rats, including three consecutive failures to return to running after contacting the shock stimulus at the rear of the treadmill and a respiratory exchange ratio Ͼ 1.015 (4).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that animals initially exposed to neonatal hyperoxia respond to adult hypoxia with increased RVH and RVSP, suggesting a more severe pulmonary hypertensive phenotype (16). In addition, we showed that compared with adult animals exposed to Hypoxia (wk [10][11][12] Re co ve ry Figure 1.…”
Section: Discussionmentioning
confidence: 63%
“…All procedures were approved by the Indiana University Animal Care and Use Committee, as previously described (16,17). SpragueDawley rat pups were exposed to either room air (RA) or continuous hyperoxia (>90% oxygen) for the first 10 postnatal days, corresponding to the period of saccular and early alveolar lung development (18), and were then returned to RA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations